Aspergillus terreus spondylodiscitis following acupuncture and acupotomy in an immunocompetent host: case report and literature review - Jin, Yufei; Yin, Xiang (Frontiers in Cellular and Infection Microbiology, 2024)
Aspergillus terreus is a fungus responsible for various infections in human beings; however, spine involvement is uncommon. Herein, we report a case of A. terreus spondylodiscitis following acupuncture and acupotomy in an immunocompetent Chinese patient. Admission lumbar magnetic resonance imaging (MRI) revealed infection at the L4/5 level without significant vertebral destruction. After unsuccessful symptomatic and anti-tuberculosis treatments, A. terreus was identified through culture, microscopy of isolate, histological examination and VITEK system. Intravenous voriconazole was then given; however, the patient’s spinal condition deteriorated rapidly, resulting in evident destruction of the L4/5 vertebral bodies. Surgeries including L4/5 intervertebral disc debridement, spinal canal decompression, posterior lumbar interbody fusion (PLIF) with allogeneic fibula ring fusion cages, and posterior pedicle screw fixation were then performed. Imaging findings at one-month and six-month follow-up suggested that the patient was successfully treated. This case highlighted two important points: firstly, although acupuncture and acupotomy are generally regarded as safe conservative treatments for pain management, they can still lead to complications such as fungal spinal infection. Therefore, vigilance is necessary when considering these treatments; secondly, PLIF with allogeneic fibula ring fusion cages may be beneficial for A. terreus spondylodiscitis patients with spinal instability.